Decavanadate and metformin-decavanadate effects in human melanoma cells - de Sousa-Coelho, Ana Luísa (2022)
Decavanadate is a polyoxometalate (POMs) that has shown extensive biological activities, including antidiabetic and anticancer activity. Importantly, vanadium-based compounds as well as antidiabetic biguanide drugs, such as metformin, have shown to exert therapeutic effects in melanoma. A combination of these agents, the metformin-decavanadate complex, was also recognized for its antidiabetic effects and recently described as a better treatment than the monotherapy with metformin enabling lower dosage in rodent models of diabetes. Herein, we compare the effects of decavanadate and metformin-decavanadate on Ca2+-ATPase activity in sarcoplasmic reticulum vesicles from rabbit skeletal muscles and on cell signaling events and viability in human melanoma cells. We show that unlike the decavanadate-mediated non-competitive mechanism, metformin-decavanadate inhibits Ca2+-ATPase by a mixed-type competitive-non-competitive inhibition with an IC50 value about 6 times higher (87 mu M) than the previously described for decavanadate (15 mu M). We also found that both decavanadate and metformin-decavanadate exert antiproliferative effects on melanoma cells at 10 times lower concentrations than monomeric vanadate. Western blot analysis revealed that both, decavanadate and metformin-decavanadate increased phosphorylation of extracellular signal-regulated kinase (ERK) and serine/ threonine protein kinase AKT signaling proteins upon 24 h drug exposure, suggesting that the anti-proliferative activities of these compounds act independent of growth-factor signaling pathways.